Public Administration in Africa performance and challenges - Vyas-Doorgapersad, Shikha (Boca Raton Talory & Francis, 2013)
Public Administration in Africa: performance and Challenges examines the complexities of the art of governance from unique African Perspective. The editors bring together a cohesive study of the major issues and regions by taking an analytic approach with strong problem-solution application. Regions addressed range from South Africa, Congo, Uganda, Nigeria, Ghana, Mauritius, and Botswana. Themes include colonialism, reform, poverty, economy, decentralization, financing, media, political structures, and more.Beginning with an analysis of the relationship of policy design and its destination, service delivery, the discusses the historical development of a state that has gone through upheavals in government and explores a decayed political economy that ultimately results in a need for sweeping measures. The text examines the issues emerging policy-makers in Africa must tackle, namely poverty and denial or lack of resources to maintain a dignified human life. It highlights how the media can be catalyst for good governance and provides analytical aspects of implementing good governance reforms. The book concludes with an examination of the concepts of decentralization and devolution in measuring service delivery performance and exploration of Africa's economic success story. It also details the African Peer Review Mechanisms in selected African Countries and provides a holistic analysis of local government functioning in Africa. These features and more make it an interdisciplinary reference for diverse economic, political and administrative issues.
Includes bibliographical references and index
Keywords: Public administration-Africa, Management-Africa